Technology dissemination for Sambel Pecel business groups in Madiun City - Prasetya, Agus; Komara, Beni Dwi; Dewi, Anggra Lita Sandra; Anshori, Shodiq (Community Empowerment, 2021)
Sambel Pecel is one of the leading products and he driving force of the Madiun City economy. In fact, it has become an export commodity to various countries such as Malaysia, Saudi Arabia, Hong Kong, Singapore, Brunei and Taiwan. The problems faced by MSMEs were the use of traditional equipment and simple packaging. This service provides several solutions to overcome these problems. First, counseling and training on the pre-production process with the implementation of a peanut grinder. Second, the production process (shop floor) with the implementation of a fryer and peanut grinder (vacuum frying). Third, re-packaging for the post-production process with modern packaging technology. This tool makes the product more durable and certainly attracts consumer interest.